American Naturalism and the Future of Philosophy - Saatkamp, Herman (Ruch Filozoficzny, 2023)
Philosophy as a discipline is facing new challenges that will determine its future. The challenges include the historic ones relating to economic conditions and administrative leadership that focuses on preparation for employment in a way that lessens the intellectual development of students. But the new challenges occur in a worldwide democratic recession and in political leadership that seems to be moving toward greater censorship and less academic freedom. In America, this is also occurring with a decline in student enrollment that negatively impacts the liberal arts and particularly philosophy. This article examines the way two forms of American naturalism may respond. John Dewey’s cultural naturalism and George Santayana’s thorough, non-reductive naturalism provide an array of alternatives. I explore alternatives open to philosophers that include abandoning philosophy by leaving the university or becoming an administrator, as well as alternatives available if one remains in the university. Finally, I offer four criteria for judging the viability of choosing any of the alternatives.